A high performance and long life low voltage cable
By adjusting the cable structure and materials, using double-layer insulation layer, fiberglass rope and water barrier paste, the cable is solved by insufficient water resistance, corrosion resistance and aging resistance in complex environments, extending the service life of the cable and reducing the economy cost.
Patent Information
- Application Number
- CN202210873675.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-21
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2042-07-21
AI Technical Summary
Existing cables are susceptible to environmental influences, resulting in short working life, especially in complex environments, insufficient water resistance, corrosion resistance and aging resistance, resulting in frequent replacement, which increases economic costs.
By adjusting the cable structure and materials, the double insulating layer obtained by using the double-layer co-extrusion process is combined with glass fiber rope and fiber wrap, and external water-blocking paste, the cable's corrosion resistance, aging resistance and water-blocking properties are improved.
It extends the service life of the cable, reduces production costs, improves the reliability and service life of the cable in complex environments, and prevents moisture from penetration and avoids moisture from cables.
Smart Images

Figure CN115424766B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of long-life cables, and in particular to a high-performance long-life low-voltage cable. Background Art
[0002] Cables are widely used in all walks of life and play an important role in people's daily lives. Therefore, the quality and performance of cable products have a significant impact. In view of the particularity of the industry and the complexity of the environment, the working environment of cables is often complex and harsh, which will lead to phenomena such as cable moisture and structural aging, which will ultimately affect the service life of the cables. Due to the limitations of material costs and processes, ordinary cables are often easily affected by the environment, resulting in rapid damage to the cables, reducing the long-term performance of the cables, and thus having a short working life. The cables need to be replaced frequently, which seriously affects the production activities of the users and greatly increases the economic costs. Therefore, under the current circumstances, it is increasingly urgent to design a high-life cable with a reasonable structure, scientific material selection, and wide applicability.
[0003] The Chinese invention patent with publication number CN109102935A discloses a high temperature resistant cable with a long service life, comprising a conductor, an insulator is arranged outside the conductor, an insulating core wire is arranged outside the insulator, and a heat insulation filling layer is arranged outside the insulating filling layer, a waterproof insulating layer is arranged outside the insulating filling layer, an isolation layer is arranged outside the waterproof insulating layer, an inner protective layer is arranged outside the isolation layer, and a heat transfer material is arranged outside the inner protective layer, and a heat barrier layer is arranged outside the heat transfer material. However, the cable can only extend its service life in a high temperature environment, while the general environment in which the cable is used requires its water resistance, corrosion resistance, aging resistance and other properties, so its application field is narrow, and its structure is complex and its economic cost is high. Summary of the invention
[0004] In order to solve the technical problem that cables are easily affected by the environment and have a short working life, the present invention provides a high-performance, long-life low-voltage cable. By adjusting the cable structure and the materials used, the corrosion resistance and aging resistance are improved while meeting the high conductivity performance, thereby extending the service life.
[0005] The specific technical solution of the present invention is: the present invention provides a high-performance, long-life low-voltage cable, including a cable core and a glass fiber tape layer and an outer sheath sequentially coated on the outside of the cable core from the inside to the outside; the cable core includes a plurality of conductors and a double insulation layer obtained by extruding the conductors using a double-layer co-extrusion process; a plurality of glass fiber ropes are filled between the cable core and the glass fiber tape layer.
[0006] The present invention adjusts the cable structure and the materials used to extend the service life while meeting the high conductivity. First, a double-layer co-extrusion package is used outside the conductor to obtain a double insulation layer, which is divided into inner and outer double-layer insulation. Different insulating materials are used to reduce production costs while improving the breakdown electric field strength, heat aging resistance, and mechanical properties, thereby extending the service life of the cable in various complex environments. In addition, glass fiber rope fillers and glass fiber wrapping tapes are used as cabling auxiliary materials. The glass fiber rope does not absorb water and has good corrosion resistance. It is not easy to mildew and has a certain tensile strength. The glass fiber tape has certain insulation properties, and has excellent corrosion resistance and aging resistance. It also has high strength and a smooth appearance. Both are excellent auxiliary materials for cable products and can greatly improve the corrosion resistance of the cable.
[0007] Preferably, the conductor is made of tinned copper wires tightly compressed and twisted.
[0008] The conductor is made of tinned copper wires twisted together, with a conductor compression coefficient greater than 90%, which increases the tightness between the conductor wires, reduces the chance of pollutants entering the conductor, and improves corrosion resistance. In addition, tinning the surface of the copper wire can greatly improve the oxidation resistance and corrosion resistance of copper.
[0009] Preferably, the double insulation layer comprises an inner insulation layer and an outer insulation layer from inside to outside; the insulation material used in the inner insulation layer is 105°C radiation cross-linked polyolefin; the insulation material used in the outer insulation layer is 125°C radiation cross-linked halogen-free low-smoke flame-retardant polyolefin.
[0010] The inner insulation uses 105℃ irradiation cross-linked polyolefin insulation material, and the outer insulation uses 125℃ irradiation cross-linked halogen-free low-smoke flame-retardant polyolefin insulation material. The production cost of the inner insulation material is relatively low, and the service life of the outer insulation material is longer. The advantages of the two are combined to better meet market demand. At the same time, when the outer insulation material burns, no halogen acid gas is released, the smoke volume is low, the toxicity is low, the flame retardant performance is good, and it will not cause pollution to the environment. Irradiation cross-linking has a good extrusion process and no pre-cross-linking is produced. The cable production speed is fast and the surface is smooth.
[0011] Preferably, the material used for the outer protective layer is radiation cross-linked UV-proof halogen-free low-smoke flame-retardant polyolefin.
[0012] The material used for the outer sheath can improve the mechanical properties, heat resistance, environmental stress cracking resistance, and UV resistance of the sheath, thereby improving the reliability and service life of the cable.
[0013] Preferably, the glass fiber tape layer and the outer protective layer are covered with an inner protective layer, an armor layer and a water-blocking layer in sequence from the inside to the outside.
[0014] Preferably, the material of the inner protective layer is nylon.
[0015] The inner sheath is made of nylon, which has excellent fatigue resistance and can maintain its original mechanical strength after repeated bending. Nylon has an extremely low water absorption rate, which can effectively reduce the infiltration of moisture into the cable and damage the stability of the cable structure.
[0016] Preferably, the material used for the armor layer is tinned brass strip.
[0017] The armor layer is made of tinned brass tape, which has good stability, corrosion resistance and oxidation resistance, and has a certain protective effect on the internal structure of the cable, and can also improve the pressure resistance and effectively prevent animals from biting. At the same time, it has a certain electronic shielding effect to prevent electromagnetic interference from the external environment.
[0018] Preferably, the water-blocking layer is formed by coating a water-blocking paste on the outside of the armor layer.
[0019] Apply water-blocking paste on the outside of the armor layer so that the water-blocking paste can penetrate into the gaps of the armor layer to form a closed environment, thereby preventing moisture from the external humid environment from penetrating into the cable during use, causing the cable to become damp and affect the use of the cable, thereby increasing its service life.
[0020] Preferably, the preparation method of the water-blocking paste comprises the following steps:
[0021] (1) Preparation of expansion material: Sodium chloride, sodium sulfate and sodium hydroxide are dissolved in water, acrylic acid and acrylamide are added and the temperature is maintained at 30-40° C. for reaction for 30-50 min, sodium persulfate and ferrous sulfate are then added, and the temperature is maintained at 50-60° C. for reaction for 5-7 h under an inert atmosphere to obtain an expansion material;
[0022] (2) Preparation of ointment: acrylamide, vinyl acetate, sodium dodecylbenzene sulfonate and potassium persulfate are added to water, reacted at 70-80°C for 40-60 minutes, and then soybean oil and isopropanol are added, and the reaction is continued for 1-3 hours; after the reaction is completed, a silane oligomer is added, wherein the silane oligomer is a polymer having a molecular weight of 2000-5000 obtained by polymerizing a vinyl-containing silane coupling agent monomer, and the mixture is distilled under reduced pressure at 90-100°C for 2-3 hours to obtain a mixture A; Melamine and formaldehyde are mixed, the pH is adjusted to 9-10, and the mixture is reacted at 70-90°C for 2-5 hours to obtain a mixture B; the mixture A is mixed with polyalphaolefin synthetic oil to obtain a mixture C; the mixture B, the mixture C and styrene-butadiene rubber are mixed so that the mass ratio of the mixture A, the polyalphaolefin synthetic oil, the mixture B and the styrene-butadiene rubber is 20-35:40-50:3-8:5-10, and then the mixture is reacted at 150-180°C for 1-3 hours to obtain an ointment;
[0023] (3) Preparation of water-blocking paste: The prepared ointment is heated to 60-80° C., an expansion material and an antioxidant are added, stirred for 1-2 h, and then ground and homogenized, and vacuumed and degassed to obtain a water-blocking paste.
[0024] The expansion material in the water-blocking paste has high water absorption, and can also be cross-linked with the free formaldehyde in the ointment, and avoid the problem of uneven dispersion and poor bonding caused by the addition of the powder of the super absorbent resin. In addition, the present invention also adds a three-dimensional network molecular chain structure to the ointment, and adopts acrylamide, vinyl acetate and the rich unsaturated fatty acids in wild soybean oil to achieve copolymerization to form a long fatty carbon chain, and the wild soybean oil has good hydrophobicity, and then formaldehyde is added for pre-crosslinking. Then, silane oligomers and melamine after methylation reaction are added for cross-linking again to form a highly hydrophobic three-dimensional network molecular chain structure, in which silane oligomers will also form Si-O-Si structure with active groups, further improving water resistance and reducing water content. Therefore, it is necessary to balance the raw material ratio in the water-blocking paste to achieve a pro-hate balance, so that it has good water absorption and expansion performance, and can also play the waterproofness of the internal network structure to prevent water molecules from penetrating into the cable core surface. In addition, the addition of copolymers and silane oligomers in the paste can also prevent the water-blocking paste from being too viscous at low temperatures or too thin at high temperatures. It has excellent blending performance and stable structure and chemical properties, so that the water-blocking paste can be used stably for a long time without oil separation.
[0025] Preferably, in step (1), the mass ratio of sodium chloride, sodium sulfate, sodium hydroxide, acrylic acid, acrylamide, sodium persulfate and ferrous sulfate is 4-8:5-10:20-30:30-50:15-30:1-2:15-25.
[0026] Preferably, in step (2), the mass volume ratio of acrylamide, vinyl acetate, sodium dodecylbenzene sulfonate, potassium persulfate, soybean oil, isopropanol, silane oligomer and water is 30-40g:9-17g:2-4g:0.5-1.5g:10-18g:30-40mL:5-10g:200mL; the mass ratio of melamine to formaldehyde is 1:1.5-2.
[0027] Preferably, in step (3), the mass ratio of the ointment, the expansion material and the antioxidant is 80-95:3-10:0.5-1.
[0028] Compared with the prior art, the beneficial effects of the present invention are:
[0029] (1) By adjusting the cable structure and materials, the service life can be extended while meeting the requirements of high conductivity;
[0030] (2) Using double-layer insulation outside the conductor and different insulating materials can reduce production costs while improving the breakdown electric field strength, heat aging resistance and mechanical properties, thereby extending the service life of the cable in various complex environments;
[0031] (3) Using glass fiber rope fillers and glass fiber wrapping tape as cable auxiliary materials, it has a certain tensile strength and excellent corrosion resistance and aging resistance;
[0032] (4) The water-blocking layer is coated with a water-blocking paste, which not only has good water absorption and expansion properties, but also can exert the waterproofness of the internal mesh structure to prevent water molecules from penetrating into the cable core surface; in addition, the structure and chemical stability are good, so that the water-blocking paste can be used stably for a long time without oil separation. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a schematic diagram of the structure of the high-performance and long-life low-voltage cable in the present invention.
[0034] The reference numerals are: conductor 1 , inner insulating layer 2 , outer insulating layer 3 , glass fiber rope 4 , glass fiber tape layer 5 , inner protective layer 6 , armor layer 7 , water blocking layer 8 , outer protective layer 9 . DETAILED DESCRIPTION
[0035] The present invention will be further described below in conjunction with the embodiments.
[0036] Overall embodiment
[0037] A high-performance, long-life low-voltage cable comprises a cable core and a glass fiber tape layer 5, an inner sheath 6, an armor layer 7, a water-blocking layer 8 and an outer sheath 9 which are sequentially coated on the cable core from the inside to the outside. The cable core comprises a plurality of conductors 1 which are tightly twisted by tinned copper wires, and a double insulating layer is obtained by extruding the conductor 1 by a double-layer co-extrusion process. The double insulating layer comprises an inner insulating layer 2 and an outer insulating layer 3 from the inside to the outside. The inner insulating layer 2 is made of 105°C irradiated cross-linked polyolefin insulating material, and the outer insulating layer 3 is made of 125°C irradiated cross-linked halogen-free, low-smoke, flame-retardant polyolefin insulating material. A plurality of glass fiber ropes 4 are filled between the cable core and the glass fiber tape layer 5. The glass fiber ropes 4 and the glass fiber wrapping tape are used as auxiliary materials for cable production, which can improve the corrosion resistance and aging resistance of the cable. Nylon extrusion is used as the inner protective layer 6 outside the glass fiber tape layer 5, and then tinned brass tape is used for armoring to obtain the armor layer 7. Water-blocking paste is coated on the outside of the armor layer 7 to obtain the water-blocking layer 8. The water-blocking paste penetrates into the gap of the armor layer 7 to form a closed environment, thereby improving the water-blocking property of the cable. Radiation-cross-linked UV-resistant halogen-free low-smoke flame-retardant polyolefin material is used as the outer protective layer 9 outside the water-blocking layer 8.
[0038] The preparation method of the water-blocking paste comprises the following steps:
[0039] (1) Preparation of expansion material: dissolving sodium chloride, sodium sulfate and sodium hydroxide in water, adding acrylic acid and acrylamide and maintaining the temperature at 30-40° C. for reaction for 30-50 min, then adding sodium persulfate and ferrous sulfate, wherein the mass ratio of sodium chloride, sodium sulfate, sodium hydroxide, acrylic acid, acrylamide, sodium persulfate and ferrous sulfate is 4-8:5-10:20-30:30-50:15-30:1-2:15-25; reacting at a temperature of 50-60° C. for 5-7 h under an inert atmosphere to obtain an expansion material;
[0040] (2) Preparation of ointment: acrylamide, vinyl acetate, sodium dodecylbenzene sulfonate and potassium persulfate are added to water, reacted at 70-80°C for 40-60 minutes, then wild soybean oil and isopropanol are added, and the reaction is continued for 1-3 hours; after the reaction is completed, a silane oligomer is added, wherein the silane oligomer is a polymer having a molecular weight of 2000-5000 obtained by polymerizing a vinyl-containing silane coupling agent monomer, and the mixture is distilled under reduced pressure at 90-100°C for 2-3 hours to obtain a mixture A; the mass volume ratio of acrylamide, vinyl acetate, sodium dodecylbenzene sulfonate, potassium persulfate, wild soybean oil, isopropanol, silane oligomer and water is 30-40g: 9-17g: 2-4g: 0.5-1.5g: 10-18g: 30-40mL: 5-10g: 200mL; melamine and formaldehyde are mixed in a mass ratio of 1:1.5-2, the pH is adjusted to 9-10, and the mixture is reacted at 70-90°C for 2-5h to obtain a mixture B; mixture A is mixed with polyalphaolefin synthetic oil to obtain a mixture C; mixture B, mixture C and styrene-butadiene rubber are mixed, the mass ratio of the mixture A, polyalphaolefin synthetic oil, mixture B and styrene-butadiene rubber is 20-35:40-50:3-8:5-10, and the mixture is reacted at 150-180°C for 1-3h to obtain an ointment;
[0041] (3) Preparation of water-blocking paste: Heat the prepared ointment to 60-80° C., add an expansion material and an antioxidant, wherein the mass ratio of the ointment, the expansion material and the antioxidant is 80-95:3-10:0.5-1, stir for 1-2 hours, and then grind and homogenize, and vacuum degas, to obtain a water-blocking paste.
[0042] Example 1
[0043] A high performance, long life low voltage cable, such as Figure 1As shown, it includes a cable core and a glass fiber tape layer 5, an inner sheath 6, an armor layer 7, a water-blocking layer 8 and an outer sheath 9 which are sequentially coated on the cable core from the inside to the outside. The cable core includes a plurality of conductors 1 which are tightly twisted by tinned copper wires. The conductor 1 is extruded by a double-layer co-extrusion process to obtain a double insulation layer. The double insulation layer includes an inner insulation layer 2 and an outer insulation layer 3 from the inside to the outside. The inner insulation layer 2 is made of 105°C irradiated cross-linked polyolefin insulation material, and the outer insulation layer 3 is made of 125°C irradiated cross-linked halogen-free low-smoke flame-retardant polyolefin insulation material. A plurality of glass fiber ropes 4 are filled between the cable core and the glass fiber tape layer 5. The use of the glass fiber ropes 4 and the glass fiber wrapping tape as cable auxiliary materials can improve the corrosion resistance and aging resistance of the cable. Nylon extrusion is used as the inner protective layer 6 outside the glass fiber tape layer 5, and then tinned brass tape is used for armoring to obtain the armor layer 7. Water-blocking paste is coated on the outside of the armor layer 7 to obtain the water-blocking layer 8. The water-blocking paste penetrates into the gap of the armor layer 7 to form a closed environment, thereby improving the water-blocking property of the cable. Radiation-cross-linked UV-resistant halogen-free low-smoke flame-retardant polyolefin material is used as the outer protective layer 9 outside the water-blocking layer 8.
[0044] The preparation method of the water-blocking paste comprises the following steps:
[0045] (1) Preparation of expansion material: 5 g of sodium chloride, 8 g of sodium sulfate and 25 g of sodium hydroxide were dissolved in 100 mL of water, 35 g of acrylic acid and 20 g of acrylamide were added and the temperature was maintained at 35° C. for 40 min, and then 1.5 g of sodium persulfate and 22 g of ferrous sulfate were added and the reaction was carried out at 60° C. for 5.5 h under a nitrogen atmosphere to obtain an expansion material;
[0046] (2) Preparation of ointment: 36 g acrylamide, 12 g vinyl acetate, 2.5 g sodium dodecylbenzene sulfonate, and 1 g potassium persulfate were added to 200 mL water, and the mixture was reacted at 80°C for 45 min. Then, 15 g wild soybean oil and 35 mL isopropanol were added and the reaction was continued for 2 h. After the reaction was completed, 6 g silane oligomer was added. The silane oligomer was a kh-570 silane coupling agent, and a polymer with an average molecular weight of 3300 was obtained by polymerization. The mixture was distilled at 100°C under reduced pressure for 2 h to obtain a mixture A. Melamine and formaldehyde were mixed in a mass ratio of 1:1.5, the pH was adjusted to 9-10, and the mixture was reacted at 80°C for 3 h to obtain a mixture B. 30 g of the mixture A was mixed with 42 g of polyalphaolefin synthetic oil to obtain a mixture C. 6 g of the mixture B, the mixture C, and 6 g of styrene-butadiene rubber were mixed and reacted at 170°C for 2 h to obtain an ointment.
[0047] (3) Preparation of water-blocking paste: 90 g of the prepared ointment was heated to 75° C., 8 g of the expansion material and 0.5 g of the antioxidant were added, and stirred for 2 h. The mixture was then ground and homogenized, and vacuumed and degassed to obtain a water-blocking paste.
[0048] Example 2
[0049] A high-performance, long-life low-voltage cable comprises a cable core and a glass fiber tape layer 5, an inner sheath 6, an armor layer 7, a water-blocking layer 8 and an outer sheath 9 which are sequentially coated on the cable core from the inside to the outside. The cable core comprises a plurality of conductors 1 which are tightly twisted by tinned copper wires, and a double insulating layer is obtained by extruding the conductor 1 by a double-layer co-extrusion process. The double insulating layer comprises an inner insulating layer 2 and an outer insulating layer 3 from the inside to the outside. The inner insulating layer 2 is made of 105°C irradiated cross-linked polyolefin insulating material, and the outer insulating layer 3 is made of 125°C irradiated cross-linked halogen-free, low-smoke, flame-retardant polyolefin insulating material. A plurality of glass fiber ropes 4 are filled between the cable core and the glass fiber tape layer 5. The glass fiber ropes 4 and the glass fiber wrapping tape are used as auxiliary materials for cable production, which can improve the corrosion resistance and aging resistance of the cable. Nylon extrusion is used as the inner protective layer 6 outside the glass fiber tape layer 5, and then tinned brass tape is used for armoring to obtain the armor layer 7. Water-blocking paste is coated on the outside of the armor layer 7 to obtain the water-blocking layer 8. The water-blocking paste penetrates into the gap of the armor layer 7 to form a closed environment, thereby improving the water-blocking property of the cable. Radiation-cross-linked UV-resistant halogen-free low-smoke flame-retardant polyolefin material is used as the outer protective layer 9 outside the water-blocking layer 8.
[0050] The preparation method of the water-blocking paste comprises the following steps:
[0051] (1) Preparation of expansion material: 5 g of sodium chloride, 8 g of sodium sulfate and 28 g of sodium hydroxide were dissolved in 100 mL of water, 45 g of acrylic acid and 26 g of acrylamide were added and the temperature was kept at 40° C. for 50 min, and then 1.5 g of sodium persulfate and 23 g of ferrous sulfate were added and the reaction was carried out at 60° C. for 6 h under a nitrogen atmosphere to obtain an expansion material;
[0052] (2) Preparation of ointment: 36 g acrylamide, 12 g vinyl acetate, 2.5 g sodium dodecylbenzene sulfonate, and 1 g potassium persulfate were added to 200 mL water, and the mixture was reacted at 80°C for 45 min. Then, 15 g wild soybean oil and 35 mL isopropanol were added and the reaction was continued for 2 h. After the reaction was completed, 6 g silane oligomer was added. The silane oligomer was a kh-570 silane coupling agent, and a polymer with an average molecular weight of 3300 was obtained by polymerization. The mixture was distilled at 100°C under reduced pressure for 2 h to obtain a mixture A. Melamine and formaldehyde were mixed in a mass ratio of 1:1.5, the pH was adjusted to 9-10, and the mixture was reacted at 80°C for 3 h to obtain a mixture B. 30 g of the mixture A was mixed with 42 g of polyalphaolefin synthetic oil to obtain a mixture C. 6 g of the mixture B, the mixture C, and 6 g of styrene-butadiene rubber were mixed and reacted at 170°C for 2 h to obtain an ointment.
[0053] (3) Preparation of water-blocking paste: 92 g of the prepared ointment was heated to 70° C. 6 g of the expansion material and 0.5 g of the antioxidant were added, stirred for 2 h, and then ground and homogenized, and vacuumed and degassed to obtain a water-blocking paste.
[0054] Example 3
[0055] A high-performance, long-life low-voltage cable comprises a cable core and a glass fiber tape layer 5, an inner sheath 6, an armor layer 7, a water-blocking layer 8 and an outer sheath 9 which are sequentially coated on the cable core from the inside to the outside. The cable core comprises a plurality of conductors 1 which are tightly twisted by tinned copper wires, and a double insulating layer is obtained by extruding the conductor 1 by a double-layer co-extrusion process. The double insulating layer comprises an inner insulating layer 2 and an outer insulating layer 3 from the inside to the outside. The inner insulating layer 2 is made of 105°C irradiated cross-linked polyolefin insulating material, and the outer insulating layer 3 is made of 125°C irradiated cross-linked halogen-free, low-smoke, flame-retardant polyolefin insulating material. A plurality of glass fiber ropes 4 are filled between the cable core and the glass fiber tape layer 5. The glass fiber ropes 4 and the glass fiber wrapping tape are used as auxiliary materials for cable production, which can improve the corrosion resistance and aging resistance of the cable. Nylon extrusion is used as the inner protective layer 6 outside the glass fiber tape layer 5, and then tinned brass tape is used for armoring to obtain the armor layer 7. Water-blocking paste is coated on the outside of the armor layer 7 to obtain the water-blocking layer 8. The water-blocking paste penetrates into the gap of the armor layer 7 to form a closed environment, thereby improving the water-blocking property of the cable. Radiation-cross-linked UV-resistant halogen-free low-smoke flame-retardant polyolefin material is used as the outer protective layer 9 outside the water-blocking layer 8.
[0056] The preparation method of the water-blocking paste comprises the following steps:
[0057] (1) Preparation of expansion material: 5 g of sodium chloride, 8 g of sodium sulfate and 25 g of sodium hydroxide were dissolved in 100 mL of water, 35 g of acrylic acid and 20 g of acrylamide were added and the temperature was maintained at 35° C. for 40 min, and then 1.5 g of sodium persulfate and 22 g of ferrous sulfate were added and the reaction was carried out at 60° C. for 5.5 h under a nitrogen atmosphere to obtain an expansion material;
[0058] (2) Preparation of ointment: 35 g acrylamide, 14 g vinyl acetate, 3 g sodium dodecylbenzene sulfonate, and 1 g potassium persulfate were added to 200 mL water, and the mixture was reacted at 80°C for 50 min. Then, 16 g wild soybean oil and 40 mL isopropanol were added and the reaction was continued for 3 h. After the reaction was completed, 8 g silane oligomer was added. The silane oligomer was a kh-570 silane coupling agent, and a polymer with an average molecular weight of 4100 was obtained by polymerization. The mixture was distilled at 100°C under reduced pressure for 2 h to obtain a mixture A. Melamine and formaldehyde were mixed in a mass ratio of 1:1.5, the pH was adjusted to 9-10, and the mixture was reacted at 85°C for 4 h to obtain a mixture B. 35 g of the mixture A was mixed with 45 g of polyalphaolefin synthetic oil to obtain a mixture C. 6 g of the mixture B, the mixture C, and 8 g of styrene-butadiene rubber were mixed and reacted at 180°C for 2 h to obtain an ointment.
[0059] (3) Preparation of water-blocking paste: 86 g of the prepared ointment was heated to 60-80° C., 8 g of the expansion material and 0.5 g of the antioxidant were added, and stirred for 1.5 h. The mixture was then ground and homogenized, and vacuumed and degassed to obtain a water-blocking paste.
[0060] Comparative Example 1
[0061] The difference from Example 1 is that there is no three-dimensional network cross-linking structure in the water-blocking paste.
[0062] The preparation method of the water-blocking paste comprises the following steps:
[0063] (1) Preparation of expansion material: 5 g of sodium chloride, 8 g of sodium sulfate and 25 g of sodium hydroxide were dissolved in 100 mL of water, 35 g of acrylic acid and 20 g of acrylamide were added and the temperature was maintained at 35° C. for 40 min, and then 1.5 g of sodium persulfate and 22 g of ferrous sulfate were added and the reaction was carried out at 60° C. for 5.5 h under a nitrogen atmosphere to obtain an expansion material;
[0064] (2) Preparation of ointment: 15 g of soybean oil, 20 g of polybutene, 55 g of poly-α-olefin synthetic oil and 8 g of styrene-butadiene rubber were mixed and stirred at 170° C. for 3 h to prepare an ointment;
[0065] (3) Preparation of water-blocking paste: 90 g of the prepared ointment was heated to 75° C., 8 g of the expansion material and 0.5 g of the antioxidant were added, and stirred for 2 h. The mixture was then ground and homogenized, and vacuumed and degassed to obtain a water-blocking paste.
[0066] Comparative Example 2
[0067] The difference from Example 1 is that no silane oligomer is added during the preparation of the water-blocking paste.
[0068] The preparation method of the water-blocking paste comprises the following steps:
[0069] (1) Preparation of expansion material: 5 g of sodium chloride, 8 g of sodium sulfate and 25 g of sodium hydroxide were dissolved in 100 mL of water, 35 g of acrylic acid and 20 g of acrylamide were added and the temperature was maintained at 35° C. for 40 min, and then 1.5 g of sodium persulfate and 22 g of ferrous sulfate were added and the reaction was carried out at 60° C. for 5.5 h under a nitrogen atmosphere to obtain an expansion material;
[0070] (2) Preparation of ointment: 36 g acrylamide, 12 g vinyl acetate, 2.5 g sodium dodecylbenzene sulfonate, and 1 g potassium persulfate were added to 200 mL water, and the mixture was reacted at 80°C for 45 min. Then, 15 g wild soybean oil and 35 mL isopropanol were added and the reaction was continued for 2 h. Then, the mixture was distilled at 100°C under reduced pressure for 2 h to obtain mixture A. Melamine and formaldehyde were mixed at a mass ratio of 1:1.5, the pH was adjusted to 9-10, and the mixture was reacted at 80°C for 3 h to obtain mixture B. 30 g mixture A was mixed with 42 g polyalphaolefin synthetic oil to obtain mixture C. 6 g mixture B, mixture C, and 6 g styrene-butadiene rubber were mixed and reacted at 170°C for 2 h to obtain ointment.
[0071] (3) Preparation of water-blocking paste: 90 g of the prepared ointment was heated to 75° C., 8 g of the expansion material and 0.5 g of the antioxidant were added, and stirred for 2 h. The mixture was then ground and homogenized, and vacuumed and degassed to obtain a water-blocking paste.
[0072] Comparative Example 3
[0073] The difference from Example 1 is that during the preparation of the water-blocking paste, too much silane oligomer is added.
[0074] The preparation method of the water-blocking paste comprises the following steps:
[0075] (1) Preparation of expansion material: 5 g of sodium chloride, 8 g of sodium sulfate and 25 g of sodium hydroxide were dissolved in 100 mL of water, 35 g of acrylic acid and 20 g of acrylamide were added and the temperature was maintained at 35° C. for 40 min, and then 1.5 g of sodium persulfate and 22 g of ferrous sulfate were added and the reaction was carried out at 60° C. for 5.5 h under a nitrogen atmosphere to obtain an expansion material;
[0076] (2) Preparation of ointment: 36 g acrylamide, 12 g vinyl acetate, 2.5 g sodium dodecylbenzene sulfonate, and 1 g potassium persulfate were added to 200 mL water, and the mixture was reacted at 80°C for 45 min. Then, 15 g wild soybean oil and 35 mL isopropanol were added and the reaction was continued for 2 h. After the reaction was completed, 16 g silane oligomer was added. The silane oligomer was a kh-570 silane coupling agent, and a polymer with an average molecular weight of 3300 was obtained by polymerization. The mixture was distilled at 100°C under reduced pressure for 2 h to obtain a mixture A. Melamine and formaldehyde were mixed in a mass ratio of 1:1.5, the pH was adjusted to 9-10, and the mixture was reacted at 80°C for 3 h to obtain a mixture B. 30 g of the mixture A was mixed with 42 g of polyalphaolefin synthetic oil to obtain a mixture C. 6 g of the mixture B, the mixture C, and 6 g of styrene-butadiene rubber were mixed and reacted at 170°C for 2 h to obtain an ointment.
[0077] (3) Preparation of water-blocking paste: 90 g of the prepared ointment was heated to 75° C., 8 g of the expansion material and 0.5 g of the antioxidant were added, and stirred for 2 h. The mixture was then ground and homogenized, and vacuumed and degassed to obtain a water-blocking paste.
[0078] Comparative Example 4
[0079] The difference from Example 1 is that during the preparation of the water-blocking paste, the molecular weight of the silane oligomer is too large.
[0080] The preparation method of the water-blocking paste comprises the following steps:
[0081] (1) Preparation of expansion material: 5 g of sodium chloride, 8 g of sodium sulfate and 25 g of sodium hydroxide were dissolved in 100 mL of water, 35 g of acrylic acid and 20 g of acrylamide were added and the temperature was maintained at 35° C. for 40 min, and then 1.5 g of sodium persulfate and 22 g of ferrous sulfate were added and the reaction was carried out at 60° C. for 5.5 h under a nitrogen atmosphere to obtain an expansion material;
[0082] (2) Preparation of ointment: 36 g acrylamide, 12 g vinyl acetate, 2.5 g sodium dodecylbenzene sulfonate, and 1 g potassium persulfate were added to 200 mL water, and the mixture was reacted at 80°C for 45 min. Then, 15 g wild soybean oil and 35 mL isopropanol were added and the reaction was continued for 2 h. After the reaction was completed, 6 g silane oligomer was added. The silane oligomer was a kh-570 silane coupling agent, and a polymer with an average molecular weight of 6200 was obtained by polymerization. The mixture was distilled at 100°C under reduced pressure for 2 h to obtain a mixture A. Melamine and formaldehyde were mixed in a mass ratio of 1:1.5, the pH was adjusted to 9-10, and the mixture was reacted at 80°C for 3 h to obtain a mixture B. 30 g of the mixture A was mixed with 42 g of polyalphaolefin synthetic oil to obtain a mixture C. 6 g of the mixture B, the mixture C, and 6 g of styrene-butadiene rubber were mixed and reacted at 170°C for 2 h to obtain an ointment.
[0083] (3) Preparation of water-blocking paste: 90 g of the prepared ointment was heated to 75° C., 8 g of the expansion material and 0.5 g of the antioxidant were added, and stirred for 2 h. The mixture was then ground and homogenized, and vacuumed and degassed to obtain a water-blocking paste.
[0084] Comparative Example 5
[0085] The difference from Example 1 is that during the preparation of the water-blocking paste, no methylated melamine is added.
[0086] The preparation method of the water-blocking paste comprises the following steps:
[0087] (1) Preparation of expansion material: 5 g of sodium chloride, 8 g of sodium sulfate and 25 g of sodium hydroxide were dissolved in 100 mL of water, 35 g of acrylic acid and 20 g of acrylamide were added and the temperature was maintained at 35° C. for 40 min, and then 1.5 g of sodium persulfate and 22 g of ferrous sulfate were added and the reaction was carried out at 60° C. for 5.5 h under a nitrogen atmosphere to obtain an expansion material;
[0088] (2) Preparation of ointment: 36 g acrylamide, 12 g vinyl acetate, 2.5 g sodium dodecylbenzene sulfonate, and 1 g potassium persulfate were added to 200 mL water, and the mixture was reacted at 80° C. for 45 min. Then, 15 g wild soybean oil and 35 mL isopropanol were added, and the reaction was continued for 2 h. After the reaction was completed, 6 g silane oligomer was added, and the silane oligomer was a polymer having an average molecular weight of 3300 obtained by polymerization of kh-570 silane coupling agent, and the mixture was distilled under reduced pressure at 100° C. for 2 h to obtain a mixture A. 30 g of the mixture A was mixed with 42 g polyalphaolefin synthetic oil to obtain a mixture C. The mixture C was mixed with 6 g styrene-butadiene rubber, and the mixture was reacted at 170° C. for 2 h to obtain an ointment.
[0089] (3) Preparation of water-blocking paste: 90 g of the prepared ointment was heated to 75° C., 8 g of the expansion material and 0.5 g of the antioxidant were added, and stirred for 2 h. The mixture was then ground and homogenized, and vacuumed and degassed to obtain a water-blocking paste.
[0090] The embodiment and the comparative example were subjected to a performance comparison test, and various properties were measured according to national standards. The test conditions and other experimental materials were the same. The test results are shown in Table 1:
[0091] Table 1
[0092]
[0093] The present invention adjusts the cable structure and the materials used to improve the corrosion resistance, aging resistance and mechanical properties while meeting the high conductivity, thereby extending the service life of the cable in various complex environments. In particular, the water-blocking paste used in the water-blocking layer can make the cable life longer. As shown in Table 1, the water-blocking paste has good water absorption and swelling properties, and can also exert the waterproofness of the internal mesh structure to prevent water molecules from penetrating into the cable core surface; in addition, the structure and chemical stability are good, so that the water-blocking paste can be used stably for a long time without oil separation. Comparative Example 1 shows that the water-blocking paste without forming a three-dimensional mesh structure can still have good water absorption performance, but its oil separation rate and water content will increase. Comparative Examples 2-4 show that silane oligomers affect the formation of a three-dimensional mesh structure, which in turn affects the hydrophilic-hydrophobic structure and the hydrophilic-repellent balance, and the water-blocking effect of the water-blocking paste decreases, and oil separation is prone to occur. Comparative Example 5 shows that not adding methylated melamine will also affect the formation of a three-dimensional mesh structure, and will also affect the bonding stability between the raw material components, thereby reducing the water-blocking effect.
[0094] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. Application of a water-blocking paste in a high-performance, long-life low-voltage cable, characterized in that: The cable includes a water-blocking layer coated with a water-blocking paste; the preparation of the water-blocking paste includes the following steps: (1) Dissolve sodium chloride, sodium sulfate and sodium hydroxide in water, add acrylic acid and acrylamide and react at 30-40°C for 30-50 minutes, then add sodium persulfate and ferrous sulfate, react at 50-60°C for 5-7 hours under an inert atmosphere to obtain an expansion material; (2) Add acrylamide, vinyl acetate, sodium dodecylbenzene sulfonate and potassium persulfate to water, react at 70-80°C for 40-60 minutes, then add soybean oil and isopropanol, and continue to react for 1-3 hours; after the reaction is completed, add silane oligomer, which is a polymer with a molecular weight of 2000-5000 obtained by polymerizing a vinyl-containing silane coupling agent monomer. The mass volume ratio of acrylamide, vinyl acetate, sodium dodecylbenzene sulfonate, potassium persulfate, soybean oil, isopropanol, silane oligomer and water is 30-40g:9-17g:2-4g:0.5-1.5g:10-18g:30-40mL:5-10g:200 mL, distill under reduced pressure at 90-100℃ for 2-3h to obtain mixture A; mix melamine and formaldehyde, adjust the pH to 9-10, and react at 70-90℃ for 2-5h to obtain mixture B; mix mixture A with polyalphaolefin synthetic oil to obtain mixture C; mix mixture B, mixture C and styrene-butadiene rubber, the mass ratio of mixture A, polyalphaolefin synthetic oil, mixture B and styrene-butadiene rubber is 20-35:40-50:3-8:5-10, react at 150-180℃ for 1-3h to obtain ointment; (3) The prepared ointment is heated to 60-80°C, an expansion material and an antioxidant are added, and the mixture is stirred for 1-2 hours. The mixture is then ground and homogenized, and vacuumed and degassed to obtain a water-blocking ointment.
2. The use of the water-blocking paste as claimed in claim 1 in a high-performance, long-life low-voltage cable, characterized in that: The cable includes a cable core and a glass fiber tape layer and an outer sheath coated on the cable core from the inside to the outside in sequence; the cable core includes a number of conductors and a double insulation layer obtained by extruding the conductors by a double-layer co-extrusion process; a number of glass fiber ropes are filled between the cable core and the glass fiber tape layer; an inner sheath, an armor layer and a water-blocking layer are coated on the glass fiber tape layer and the outer sheath in sequence from the inside to the outside; the water-blocking layer is formed by coating the armor layer with a water-blocking paste.
3. The use of the water-blocking paste in high-performance, long-life low-voltage cables as claimed in claim 2, characterized in that: The conductor is made of tinned copper wires tightly compressed and twisted.
4. The use of the water-blocking paste in high-performance, long-life low-voltage cables as claimed in claim 2, characterized in that: The double insulating layer comprises an inner insulating layer and an outer insulating layer from inside to outside; the insulating material used in the inner insulating layer is 105°C irradiation cross-linked polyolefin; the insulating material used in the outer insulating layer is 125°C irradiation cross-linked halogen-free low-smoke flame-retardant polyolefin.
5. The use of the water-blocking paste in high-performance, long-life low-voltage cables as claimed in claim 2, characterized in that: The material used for the outer protective layer is radiation cross-linked UV-proof halogen-free low-smoke flame-retardant polyolefin.
6. The use of the water-blocking paste in high-performance, long-life low-voltage cables as claimed in claim 2, characterized in that: The material used for the inner protective layer is nylon.
7. The use of the water-blocking paste in high-performance, long-life low-voltage cables as claimed in claim 2, characterized in that: The material used for the armor layer is tinned brass strip.
8. The use of the water blocking paste in high-performance, long-life low-voltage cables as claimed in claim 1, characterized in that: In step (1), the mass ratio of sodium chloride, sodium sulfate, sodium hydroxide, acrylic acid, acrylamide, sodium persulfate and ferrous sulfate is 4-8:5-10:20-30:30-50:15-30:1-2:15-25; In step (2), the mass ratio of melamine to formaldehyde is 1:1.5-2; In step (3), the mass ratio of the ointment, the expansion material and the antioxidant is 80-95:3-10:0.5-1.
9. The use of the water blocking paste in high-performance, long-life low-voltage cables according to claim 1, characterized in that: In step (2), the vinyl-containing silane coupling agent monomer is KH-570.
10. The use of the water blocking paste in high-performance, long-life low-voltage cables according to claim 1, characterized in that: In step (2), the average molecular weight of the silane oligomer is 3300 or 4100.
